Coronary volume to left ventricular mass ratio in patients with diabetes mellitus - Kuneman Jurrien H; Mahdiui Mohammed El; Rosendael Alexander R Van; van den Hoogen Inje J; Patel Manesh R; Nørgaard Bjarne Linde; Fairbairn Timothy A; Koen Nieman; Takashi Akasaka; Berman Daniel S; Hurwitz Lynne M. Koweek; Pontone Gianluca; et al. (Elsevier, 2022)
Background
Diabetes mellitus is a major risk factor for coronary artery disease (CAD) and may provoke structural and functional changes in coronary vasculature. The coronary volume to left ventricular mass (V/M) ratio is a new anatomical parameter capable of revealing a potential physiological imbalance between coronary vasculature and myocardial mass. The aim of this study was to examine the V/M derived from coronary computed tomography angiography (CCTA) in patients with diabetes.
Methods
Patients with clinically suspected CAD enrolled in the ADVANCE (Assessing Diagnostic Value of Non-invasive FFRCT in Coronary Care) registry and known diabetic status were included. Coronary artery volume and left ventricular myocardial mass were analyzed from CCTA and the V/M ratio was calculated and compared between patients with and without diabetes.
Results
Of the 3053 patients (age 66 ​± ​10 years; 66% male) with known diabetic status, diabetes was present in 21.9%. Coronary volume was lower in patients with diabetes compared to those without diabetes (2850 ​± ​940 ​mm3 vs. 3040 ​± ​970 ​mm3, p ​< ​0.0001), whereas the myocardial mass was comparable between the 2 groups (122 ​± ​33 ​g vs. 122 ​± ​32 ​g, p ​= ​0.70). The V/M ratio was significantly lower in patients with diabetes (23.9 ​± ​6.8 ​mm3/g vs. 25.7 ​± ​7.5 ​mm3/g, p ​< ​0.0001). Among subjects with obstructive CAD (n ​= ​2191, 24.0% diabetics) and non-obstructive CAD (16.7% diabetics), the V/M ratio was significantly lower in patients with diabetes compared to those without (23.4 ​± ​6.7 ​mm3/g vs. 25.0 ​± ​7.3 ​mm3/g, p ​< ​0.0001 and 25.6 ​± ​6.9 ​mm3/g vs. 27.3 ​± ​7.6 ​mm3/g, respectively, p ​= ​0.006).
Conclusion
The V/M ratio was significantly lower in patients with diabetes compared to non-diabetics, even after correcting for obstructive coronary stenosis. The clinical value of the reduced V/M ratio in diabetic patients needs further investigation.